2021
DOI: 10.1002/wat2.1528
|View full text |Cite
|
Sign up to set email alerts
|

Human impact and ecosystemic health at Lake Baikal

Abstract: Lake Baikal in eastern Siberia is the deepest and (by volume) largest lake on Earth. Among the most ancient lakes, it is home to thousands of endemic species. Lake Baikal is well‐known for its water purity, especially its dominant deep‐water layers, which consist of pristine, drinking‐quality water and is inhabited by unique endemics with enormous biodiversity. But some coastal sites of this giant lake (mainly localized in isolated shallow bays and littoral zones close to settlements and industrial sites) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 124 publications
0
10
0
Order By: Relevance
“…It has been evident for more than a decade (e.g., Williamson et al, 2009) that climate change is generating complex responses in aquatic ecosystems that vary according to their geographic distribution, magnitude, and timing across the global landscape. Climate change, in particular global warming and increasing aridity, is leading to an increase of fires and fire severity (Brown et al, 2021). At the same time wildfires are also a cause of the continuing process of global climate change, by reducing forest cover and emitting greenhouse gases (e.g., CO 2 and CO) (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been evident for more than a decade (e.g., Williamson et al, 2009) that climate change is generating complex responses in aquatic ecosystems that vary according to their geographic distribution, magnitude, and timing across the global landscape. Climate change, in particular global warming and increasing aridity, is leading to an increase of fires and fire severity (Brown et al, 2021). At the same time wildfires are also a cause of the continuing process of global climate change, by reducing forest cover and emitting greenhouse gases (e.g., CO 2 and CO) (Liu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…According to Safronov (2020), the Baikal basin lost more than 12% of its forests between 2013 and 2018. Severe fires contributed to the degradation of both terrestrial and aquatic ecosystems by increasing watershed loading of sediments, nutrients and pollutants as well as by introducing smoke pollutants into the atmosphere (Brown et al, 2021). Consequently, lake Baikal, the deepest and largest lake (by volume) on earth, currently in oligotrophic state, might be receptive to wildfires effects, such as sediments and nutrients runoff to river and lake waters (Brown et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a number of integrity issues have been raised to now because of concerning pollution levels . Particularly, anthropogenic emissions from the more populated southern basin have been shown to affect the water and air quality. Moreover, it has been observed that the number of wildfires (WF), which naturally occur in that region, and the size of the area burned have increased over the past decades. ,, Hence, anthropogenic emissions pose directly and indirectly a threat to the ecosystem of Lake Baikal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it suffers from forest fires of different origins [60][61][62][63]. The industrial activity that develops in the region, mainly near urban settlements, certainly affects the quality of the environment [64][65][66]. This unique natural object, BNT, is observed by various means [44,63,[67][68][69][70][71].…”
Section: Introductionmentioning
confidence: 99%